2017
DOI: 10.1159/000485279
|View full text |Cite
|
Sign up to set email alerts
|

Bufalin Inhibits Cellular Proliferation and Cancer Stem Cell-Like Phenotypes via Upregulation of MiR-203 in Glioma

Abstract: Background/Aims: Prior studies have shown that bufalin inhibits cellular proliferation and induces apoptosis in various human cancers. MicroRNA-203 (miR-203) has been shown to function as an important regulator of tumor progression at various stages. In this study, we investigated the effect of miR-203 expression and bufalin treatment on glioma cell proliferation and stem cell-like phenotypes. Methods: We used cell viability assay, colony formation assay, cell apoptosis assay and neurosphere formation assay to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 31 publications
1
22
0
Order By: Relevance
“…Neurosphere culture cells were grown in stem cell medium consisting of DMEM/F12 (Gibco) supplemented with 1% N2, 2% B27 (Invitrogen), 20 ng/mL epidermal growth factor, and fbroblast growth factor-2 (Invitrogen) as previously indicated [23].…”
Section: Cellular Physiology and Biochemistrymentioning
confidence: 99%
“…Neurosphere culture cells were grown in stem cell medium consisting of DMEM/F12 (Gibco) supplemented with 1% N2, 2% B27 (Invitrogen), 20 ng/mL epidermal growth factor, and fbroblast growth factor-2 (Invitrogen) as previously indicated [23].…”
Section: Cellular Physiology and Biochemistrymentioning
confidence: 99%
“…One of these important miRNAs is miR-203. Previous studies have shown that miR-203 exhibits potent antiproliferative function [18][19][20] and is involved in regulating the balance between stem cell proliferation and terminal differentiation in skin cells, by targeting p63 when stem cells in the epidermis are proliferating and differentiating into stratified epithelium [21]. miR-203 has the highest level of expression in the skin [22].…”
Section: Introductionmentioning
confidence: 99%
“…Clinical reports revealed that GJXLT can prolong the median survival time in NSCLC patients [ 13 , 14 ]. Pharmacological experimental studies have demonstrated that the effective components of the herbs in GJXLT formula, such as bufalin of Corium Bufonisgecko and ginsenoside of Ginseng, play a vital role in the anti-tumor effect by inhibiting cellular proliferation [ 18 , 19 ]. In this study, we confirmed the anti-tumor efficacy of GJXLT.…”
Section: Discussionmentioning
confidence: 99%